The Effect of Highway Traffic on Heavy Metal Content of Cow Milk and Cheese (Hungarian Journal of Industry and Chemistry, 2011)
Human exposure to heavy metal elements through milk and dairy products may have influences on food safety. Although certain elements such as zinc, chromium are essential in small quantities, in high amount they can result in toxic effects on animal and human health. In this experiment samples of raw cow milk were collected from dairy farms close to highways in the central region of Hungary, and in rural green regions in West Hungary. Concentrations of selected heavy metals such as As, Cd, Cr, Cu, Fe, Mn, V, Ni, Pb and Zn in cow milk and cheese were determined using inductively coupled plasma mass spectrometry and inductively coupled plasma-optical emission (spectrometry). Chrome, copper, iron, vanadium, manganese, cadmium, arsenic, and lead content showed higher concentrations in the milk from intensive traffic areas than those in the milk from non-polluted green areas. However, in the cheese only copper, chrome, iron and lead concentrations were found significantly higher in the highway samples than those in non-polluted green samples.